2017
DOI: 10.21640/ns.v9i19.823
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de la variedad, portainjerto y época de cosecha en la calidad e índices de madurez en pimiento morrón

Abstract: Influencia de la variedad, portainjerto y época de cosecha en la calidad e índices de madurez en pimiento morrón Influence of the variety, rootstock and harvest time on the quality and maturity indices in Bell pepper Resumen IntroducciónEl uso de portainjertos para la producción de hortalizas es una técnica que ha ido en aumento en los últimos años, generando resistencia a patógenos y aumentando la producción en los cultivos.Sin embargo, hoy en día la producción no lo es todo en el rubro comercial; no basta so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Sánchez Solana [45] obtained similar results and found a positive effect of the rootstock on the fruit size. Furthermore, Palacio and Sánchez [14] found significant differences in fruit weight in the Jeanette variety grafted with Terra-no during two different harvest seasons, showing increases of over 5% compared to the non-grafted plants of the same variety. This difference is crucial for distinguishing between L and XL-sized fruits.…”
Section: Yield Componentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Sánchez Solana [45] obtained similar results and found a positive effect of the rootstock on the fruit size. Furthermore, Palacio and Sánchez [14] found significant differences in fruit weight in the Jeanette variety grafted with Terra-no during two different harvest seasons, showing increases of over 5% compared to the non-grafted plants of the same variety. This difference is crucial for distinguishing between L and XL-sized fruits.…”
Section: Yield Componentsmentioning
confidence: 95%
“…The main advantage of grafting is that it does not contaminate the environment [6], favoring the elimination of biocides. Currently, studies on grafts have reported significant advances in the field of vegetables [14]. For instance, the potential to increase important properties for human consumption, such as certain amino acids [15], product safety, nutraceutical content [16] and some antioxidants [17,18].…”
Section: Introductionmentioning
confidence: 99%